War, Love and Marriage. John Marshall and His Dearest Polly - Daszyńska, Jolanta A. (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
Mary Willis Ambler was the second of five girls born to Rebecca Burwell and Jacquelin Ambler, a prominent Yorktown family. She grew up learning many of the traditional lessons of girls at the time. John Marshall was born at Germantown in Fauquier County, on the Virginia frontier. He was the oldest of 15 children of Colonel Thomas Marshall and Mary Randolph Keith. As a boy he was taught by his father, next by a visiting clergyman who lived with the family for about a year and for a few months at an academy in Westmoreland county. For six months, during the American Revolutionary War, he studied law at William and Mary College. He served in the Continental Army under George Washington, first as a lieutenant and then as captain. Licensed to practice law in August 1780, Marshall returned to Fauquier county. He was elected to the Virginia House of Delegates in 1782. Attending the sessions of the legislature in the state capital at Richmond, he established a law practice there. Family tradition holds that Marshall fell in love with Mary soon after meeting her, and after spending time with her at dances he asked her to marry him, but she refused. As soon as she realized her error she send a cousin riding after Marshall to give him a lock of her hair. John returned it entwined with a lock of his own encased in a gold locket. They got married in 1783, had ten children, but not all of them survived to adulthood. Marshall loved Mary very much calling her my dearest Polly and spent with her 49 years of marriage. On the day of her death, she tried to remove the locket from around her neck, but being so weak John had to help her. Polly asked him to wore the locket. He wore it until his death.